Socioeconomic Factors Associate with Smoking among Rural Adult Population in Negeri Sembilan, Malaysia - Rubiah, Ajan; Muhamad Hanafiah, Juni; HS, Minhat; Aidalina, M (The Community Health Society Malaysia (CHSM), 2016)
ABSTRACT